Single cell transcriptome revealed tumor associated antigen (TAA) profile in lung adenocarcinoma (LUAD) - Fang Lv; Xueying Wu; Jin Song; Pan Wang; Shucheng Ren; Wei Guo; Qi Xue; Henghui Zhang; Jun Zhao (BMC, 2021)
Abstract It has been suggested that the heterogeneity of TAAs in lung cancer may affect the therapeutic response and disease progression. Up to now, several tumor-associated antigen (TAA)-based cancer vaccines have been investigated in lung adenocarcinoma (LUAD); however, most of them have failed at the stage of clinical trials. The present study suggests that inter-tumoral heterogeneity of TAAs is large at single-cell resolution, while the communication between tumor cells and infiltrating T cells is closely related to the expression profile of TAAs.